Effects of binders on electrochemical performance of nitrogen-doped carbon nanotube anode in sodium-ion battery. (20th August 2015) - Fan, Qingjie; Zhang, Wuxing; Duan, Jian; Hong, Kunlei; Xue, Lihong; Huang, Yunhui
Graphical abstract: Highlights: N-doped hollow carbon nanotubes (N-CNTs) are fabricated as anode for sodium-ion battery. Water soluble sodium polyacrylate (Na-PAA) and traditional organic poly(vinylidene difluoride) (PVDF) are comparatively investigated as binders of N-CNTs. Na-PAA binder can effectively improve the electrochemical performance of N-CNTs. Electrochemical activity, low internal resistance and homogeneously formed solid electrolyte interface are responsible for the improvement by Na-PAA. Abstract: N-doped hollow carbon nanotubes (N-CNTs) with turbostratic structure are prepared as anode materials for sodium-ion battery. The effects of sodium polyacrylate (Na-PAA) and poly(vinylidene difluoride) (PVDF) binders on electrochemical performance are comparatively investigated. The obtained N-CNTs have disordered carbon structure and contain N-, O-functional groups, which electrochemical performance strongly depends on the binder used. The N-CNTs electrode with Na-PAA binder exhibits large capacity, high initial coulombic efficiency, excellent cycling stability and rate performance. Compared with the traditional PVDF binder, the water soluble Na-PAA binder shows electrochemical activity, lower internal resistance, and homogeneously formed solid electrolyte interface. Further investigations show that the binding capability of Na-PAA is closely related to the molecular weight. The Na-PAA with moderate molecular weight is more suitable as the binder of sodium-ion batteries with N-CNTs anode.